Meanings of sitting in the context of chronic disease: Critical reflection on sedentary behaviour, health, choice and enjoyment - Amie Weedon; Paula Saukko; John Downey; Mark W. Orme; Dale Esliger; Sally Singh; Lauren Sherar (2019)
Reducing sedentary behaviour or sitting is a new public health focus. Emerging research has, however, found that sedentary activities may be associated with health and mental health benefits for older adults. This article reports findings of the qualitative arm of a feasibility trial to reduce sedentary behaviour among patients with Chronic Obstructive Pulmonary Disease (COPD). From interviews (n=21) conducted prior to the intervention we identified three themes: (i) participants sat to enable them to perform activities, such as housework, (ii) sitting, such as watching TV or fishing, was experienced as enjoyable, and (iii) the most ill participants experienced sitting in terms of sadness, as the only thing they could do. Our observations draw attention to three issues. First, our participants did not always sit out of choice, they had to rest between activities and sat due to breathlessness and mournfulness. Second, the intrinsic value of enjoyment associated with sedentary activities comes into sharp relief in the context of progressive chronic disease, which makes it increasingly difficult to enjoy any activity or life. Third, trials, predicated on trying out a pre-defined solution, are particularly challenging for mixed methods qualitative research seeking to trouble categories, such as choice, health and enjoyment. In conclusion we concur with research that has highlighted that sedentary activities may also have benefits, however, we would make a stronger case for appreciating alternative values, such as enjoyment of life, rather than just health, when appropriate, in research and in practice.–